29.1: Solution‐Processed Poly‐Si TFTs at Paper Compatible Temperatures. Issue 1 (June 2015) - Trifunovic, Miki; Zhang, Jin; van der Zwan, Michiel; Shimoda, Tatsuya; Ishihara, Ryoichi
Abstract : Printed TFTs made from organic and metal‐oxide semiconductors have much inferior electrical performance and reliability than their silicon counterparts. Cyclopentasilane is a liquid compound that has been found to transform into solid silicon after a UV polymerization and thermal annealing step of 350°C, making it possible for silicon devices to be printed, a much more simple and inexpensive method owing to the additive process. This thermal annealing, however, is too high for inexpensive substrates such as PET, PEN or paper. In this work we have for the first time produced poly‐silicon and TFTs at a maximum temperature of 150°C using the liquid silicon ink and an excimer laser annealing process instead of a thermal annealing step. We have formed poly‐silicon on inexpensive paper substrates. This could lead to new applications such as biodegradable high‐speed ID‐tags with a sensor for Internet of Things, which can be mass‐produced at very low‐costs by a roll‐to‐roll manufacturing process.